Cumhuriyet dönemi’nde kız teknik okullarının ekonomiye katkıları ve kalkınma planların - Uzun, Nebile Funda (My University, 2002)
Türkiye'de mesleki eğitimin gelişimini, Cumhuriyet Öncesi ve Cumhuriyet Sonrası olmak üzere iki ana bölümde incelemek gerekir. Cumhuriyet öncesinde, meslek eğitimi baba mesleğini sürdürme, çırak-kalfa-usta biçimindedir. XIII. yüzyıl başlarından itibaren Ahilik Teşkilatı ile sürdürülmüş, Osmanlı İmparatorluğu Döneminde de Ahi Teşkilatı ve Gedik Teşkilatı ile birlikte meslek eğitimi devam etmiştir. Cumhuriyet Döneminde ise; gelişmiş ve sanayileşmiş ülkeler seviyesine ulaşmak amacıyla yabancı uzmanlar davet edilmiş, onların incelemeleri ve önerileri doğrultusundan hareketle, mesleki ve teknik eğitimde, okul sayısı ve bölümleri artırılarak pek çok yenilikler yapılmıştır. 1927 yılında meslek okullarının idaresi Milli Eğitim Bakanlığı'na devredilmiştir. Türk Milli Eğitim sistemi örgün ve yaygın eğitim kurumlarını kapsar. Örgün eğitim kurumları; okul öncesi eğitim, ilköğretim, ortaöğretim ve yükseköğretim kurumlarından oluşur. Ortaöğretim kurumları; genel ve mesleki-teknik ortaöğretim kurumları olmak üzere ikiye ayrılır. Yaygın eğitim kurumları; örgün eğitime hiç katılmamış, halen bir örgün eğitim kurumuna devam eden ya da örgün eğitim sisteminden çıkmış olan kişilere verilen genellikle kısa süreli bir eğitim türüdür. Bugünkü mesleki ve teknik öğretimin yapısı, organizasyonu, ilgili kanunlar, finansmanı, okul, öğrenci ve öğretmen sayıları metin içinde ayrıntılı biçimde açıklanmış, tablolarda gösterilmiştir. EXTRACT The progress of the professionel education in Turkey has two main periods: -Pre Republic Period -Post Republic Period In the Pre Republic period, people had the prefessional in the relation of apprentice, assistant master and master. An apprentice's master was generally his father. At the beginning of the 13th century, Ahilik Teskilati had been established and in Ottoman Empire Period, professional education had been lasted by Ahilik Teskilati and Gedik Teskilati. At the time of the Republic Period, in order reach the level of developed and industrialized countries, some foreign experts had been invited to Turkey. According to the results of these experts' studies and their advices, so many innovations had been made and the number of schools and departments had been increased in professional and technical education. The control of the professional education had been left to the Ministry of National Education in 1927. Turkish National Education System has two kind of institutions: Organized Educational Institutions and Common Educational Institutions. Organized Educational Institutions has four parts: preschool education, primary education, secondary education and higher education. Secondary Education Institutions has two sections: - General secondary education institutions -Professional-technical secondary education institutions. Common education institutions train people who -has never attained to an organized education -continues to an organized educational institution -has left an organized educational instution. It is generally a short-term education. The present construction, organization, the finance and the number of schools, students, teachers of the professional and technical education have been given in the text and tables in details. The historical progress, the time and the place of the establishment, the number of schools, students and teachers and the financial structure of the professional and technical education for girls have been given in the text in details. The historical progress of the technical education for girls has been studied in Prerepublic period and Republic period. The goal and mission of these schools has been notified. The goals of the Five Years Development Plans and the decisions taken in the National Educational Councils related to to Technical Educations for girls have been notifed by years. Additional -the simplfied speech of Mithat Pasa, given in the opening of İstanbul Sultanahmet Sanat Okulu, -the life of Mithat Paşa, -the historical progress of the technical education for girls, -the organisation schema of The General Directorate for Technical Education for Girls has been notified.
Keywords: Eğitim; Ekonomi; Ekonomik durum ve koşullar